Experimental investigation of capillary force in a novel sintered copper mesh wick for ultra-thin heat pipes. (25th March 2017) - Tang, Yong; Tang, Heng; Li, Jie; Zhang, Shiwei; Zhuang, Baoshan; Sun, Yalong
Highlights: A novel sintered copper mesh wick was developed for improving the performance of ultra-thin heat pipes. Capillary force of the deposited wick structures was experimentally examined by comparing with normal mesh wicks. The capillary force of the deposited wick structures was larger than that of a normal wick. Abstract: A novel sintered copper mesh wick, fabricated by weaving, chemical deposition, and sintering, was developed for improving the performance of ultra-thin heat pipes. Capillary force of the deposited wick structures was experimentally examined by comparing with normal mesh wicks. In this study, the sintering process was used to enhance the adhesive strength of the surface structure. Capillary rate-of-rise tests with ethanol and acetone were performed to characterize the capillary force of wick structures. An infrared (IR) thermal imaging method was utilized to monitor the capillary rise processes. The effects of deposition time and sintering temperature on the capillary force were investigated. Test results indicate that the capillary force of the deposited wick structures was larger than that of a normal wick, and the rising velocity and capillary rise height increased as the deposition time increased from 5 to 20 min. The sintering process maintains good integrity of the surface microstructures even after being subjected to ultrasonic vibrations for 2 min, and also has a great influence on the capillary force of the deposited samples. The deposited wicks can achieve optimum operating efficiency by choosing deposition time of about 15 min and a sintering temperature of around 500 °C.